The The role and impact of Aluminium oxide nanoparticles in crime investigation: Dr. Syeda Mona Hassan - Dr. Syeda Mona Hassan; Malik, Dr. Aftab Ahmad; Zermina Khalid (International Journal for Electronic Crime Investigation, 2022)
Nanotechnology is an important and powerful tool in most the areas including medicine, imaging, andforensic sciences. It is rapidly growing region of research with potential in various fields, running frommedical care to production and physical science. Nanotechnology has a potential to make significantpositive contribution in forensic science in crime detection. Forensic science applies knowledge andmethods from natural science in order to identify, individualize, and assess evidence. Hence, with theaid of evidence, crime scenes can be rebuilt, investigations can be directed, and offenders can be prose-cuted. Nano-analysis use tools like UV Vis spectroscopy, atomic force microscope (AFM), XRD,EDX, Raman micro spectroscopy (Raman), scanning electron microscope (SEM), and transmissionelectron microscope (TEM) (Raman). Moreover, in current article, an attempt was made to elucidatehow nanotechnologies could be crucial in addressing current forensic investigation issues such asexplosive detection, forensic toxicological analysis, finger print analysis, forensic DNA analysis, detec-tion of explosive residue, forensic nano trackers, drug facilitated crime.